1969
DOI: 10.1017/s002217240004211x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of methods for the diagnosis of respiratory virus infections in childhood

Abstract: SUMMARYNasopharyngeal secretions and cough/nasal swabs were taken from 111 children admitted to hospital in Newcastle upon Tyne with acute lower respiratory disease. A comparison was made between nasopharyngeal secretions and cough/nasal swabs as material for isolation of viruses in tissue culture. These results were, in turn, compared with those obtained by applying a fluorescent antibody technique to the exfoliated cells in the nasopharyngeal secretions for the rapid diagnosis of respiratory syncytial virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Whenever possible, a second secretion was obtained from the patient after an interval of approximately 7 days. The method of collection and preparation of secretions has been fully described elsewhere (Sturdy, McQuillin & Gardner, 1969;Scott & Gardner, 1970).…”
Section: Patientsmentioning
confidence: 99%
“…Whenever possible, a second secretion was obtained from the patient after an interval of approximately 7 days. The method of collection and preparation of secretions has been fully described elsewhere (Sturdy, McQuillin & Gardner, 1969;Scott & Gardner, 1970).…”
Section: Patientsmentioning
confidence: 99%
“…Because of very rapid multiplication, cells from the first five passages would have been Although cough swabs and not nasopharyngeal secretions were used in these earlier studies, the use of secretions would be expected to increase the isolation rate by only about 5% (Sturdy et al, 1969). We concluded that the HL cells used in our comparison were probably of maximal sensitivity.…”
Section: Resultsmentioning
confidence: 96%
“…This communication covers the period from February 1968 to November 1970. The clinical categories used and the precise method of obtaining both nasopharyngeal secretions and cough/nasal swabs have been described (Gardner et al, 1960;Sturdy et al, 1969), and the immunofluorescent techniques are also identical with those used in our earlier studies McQuillin and McQuillin et al, 1970). During the period when the occurrence of parainfluenza virus infections were most frequent, between September 1969 and November 1970, all specimens suitable for examination by immunofluorescence were investigated for parainfluenza virus types 1, 2, and 3 when appropriate.…”
Section: Methodsmentioning
confidence: 91%